Exploring technological alternatives of nutrient recovery from digestate as a secondary resource. (December 2020) - Barampouti, E.M.; Mai, S.; Malamis, D.; Moustakas, K.; Loizidou, M.
Abstract: The valorisation of anaerobic digestate in the context of circularity and sustainability is a very challenging issue, given its increasing production rate. The main aim of this paper was to study the established and emerging technological alternatives considering anaerobic digestate as secondary resource for nutrients recovery. Initially, after mapping the composition of digestate, elevated fluctuations of nutrients content were revealed. Nitrogen content ranged from 1.6 to 21% (dry base) and phosphorous from 0.1 to 3.5% (dry base), reflecting its potential to be used as feedstock in new value chains for the production of higher value bio-based fertilisers through a multi-stakeholder and zero waste approach in line with circular economy. The current state of knowledge that was collected was then synthesized into two scenarios under the concept of integrated biorefineries that would allow the production of bio-based products, ready to enter new supply chains. Highlights: Up to date information on the composition of anaerobic digestate. Established and emerging technological approaches for nutrients recovery. Bio-based materials and fertilizers from digestate valorisation. Two scenarios for integrated biorefinery recovering nutrients from digestate.